2017
DOI: 10.1155/2017/1953076
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Crown-Rump Length and Embryonic Volume of Fetuses with Structural Congenital Abnormalities Measured in Virtual Reality: An Observational Study

Abstract: Background. With the introduction of three-dimensional (3D) ultrasound it has become possible to measure volumes. The relative increase in embryonic volume (EV) is much larger than that of the crown-rump length (CRL) over the same time period. We examined whether EV is a better parameter to determine growth restriction in fetuses with structural congenital abnormalities. Study Design, Subjects, and Outcome Measures. CRL and EV were measured using a Virtual Reality (VR) system in prospectively collected 3D ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…One possible explanation of this finding is the exclusion of pregnancies with fetal aneuploidy, congenital anomalies and fetal demise from the study population according to study design. Since the prior conditions have been associated to delayed fetal growth [14][15][16], it is not surprising that this exclusion might deflate the expected rates of preterm birth in this subgroup of fetuses. The incidence of preterm birth estimated in our study is in accordance with the reported national rates in Sweden and other Nordic countries [7,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation of this finding is the exclusion of pregnancies with fetal aneuploidy, congenital anomalies and fetal demise from the study population according to study design. Since the prior conditions have been associated to delayed fetal growth [14][15][16], it is not surprising that this exclusion might deflate the expected rates of preterm birth in this subgroup of fetuses. The incidence of preterm birth estimated in our study is in accordance with the reported national rates in Sweden and other Nordic countries [7,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Constraint (6) ensures that when the fixed resources are exhausted, then the temporary resources can be used; constraint (7) ensures that temporary resource points that transported the number of resources in each disaster area should be less than the number of its reserves; constraint (8) ensures avoiding wasting (the number of supplies to disaster areas should be less than the demand); constraint (9) shows that the distribution of materials should be positive and ℎ is a binary value.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Thus the emergency facility location is a multiobjective optimization problem which has to take quantities of complex factors into consideration, while the evolutionary algorithms such as GA [9], PSO [10], NSGA [11], and MOEA/D [12] are usually applied to solve such kind of problems. Gadhvi et al [13] presented a constrained multiobjective optimization problem which is solved by NSGA-II, SPEA2, and PESA-II; the results show that NSGA-II is able to yield a better Pareto front.…”
Section: Introductionmentioning
confidence: 99%
“…During first trimester of pregnancy, crown rump length (CRL) and embryonic volumes measurements are considered as reliable elements in detecting the gestational age 4 .…”
Section: Introductionmentioning
confidence: 99%